Rationalising the Digital Public Sphere - Almuqren, Abdullah (Advances in Social Sciences Research Journal, 2024)
This paper explores the suitability of Jürgen Habermas' concepts about the rationality of communicative actions in relation to the Internet and social media. The paper investigates the contemporary digital realm, analysing whether it functions as an expansion of the public sphere classic conceptualised by Habermas, with the aim of improving the level of rational communication. To accomplish this, the paper analyses the characteristics of the digital era, exploring Habermas's stance on social media and contemporary media. The paper analyses Habermas's concepts about the rationality of communication and supports the arguments with relevant literature to investigate the impact of current communication tools, including the Internet and its applications, on enhancing the quality of rational discourse. In order to accomplish this, it is important to thoroughly examine the key subjects pertaining to Habermas's philosophy of communication and assess its relevance to the modern virtual public sphere.